Overcoming Barriers to Corporate Training: A Strategic Framework for Success - Lee, Zion (New Advances in Business, Management and Economics Vol. 6, 2025)
The term “training” pertains to a form of learning that aims to enhance specific job-related skills in an employee’s present position. On the other hand, “development” encompasses a wider range of knowledge and abilities that are geared towards long-term career advancement and progression within an organisation. Organisations face significant challenges in implementing effective training programs. This paper aims to analyse the challenges faced by organisations in implementing effective corporate training programs. It examines common issues such as limited budgets, employee resistance, and difficulty measuring impact. The primary objective of this study is to present a comprehensive framework for addressing persistent training obstacles by doing a thorough analysis of the difficulties, offering evidence-based solutions, and recommending avenues for future improvement. The study employed a qualitative literature review methodology to examine the difficulties encountered in corporate training programmes and suggest potential remedies. A comprehensive analysis was conducted by reviewing more than 40 publications published between 1985 and 2022 to determine the prevailing issues that have been reported in previous studies. To address budget constraints, the paper proposes communicating the return on investment from training. Various metrics for evaluating impact and return on investment are also discussed. To overcome resistance, training needs to be designed as practical and relevant. The implementation of comprehensive needs assessments before the development of training programmes is also essential for achieving favourable outcomes. The paper concludes that adopting a strategic approach targeting the root causes of these challenges can maximise the effectiveness of training in developing employee skills and improving organisational performance. By leveraging suitable resources, implementing well-structured programmes, and establishing quantifiable outcomes, firms may maximise the advantages derived from efficient employee training and development. Future research should explore the optimal strategies used by industries that have successfully implemented training and development initiatives.